Starch Concentrations in Grapevine Leaves, Berries and Roots and the Effect of Canopy Management - Hunter, J.J.; Ruffner, H.P.; Volschenk, C.G. (South African Journal of Enology and Viticulture, 2017)
Diurnal and seasonal starch changes in leaves, berries and roots of Vitis vinifera L. cv. Cabernet Sauvignon/99 Richter and the effect of canopy management (a combination of suckering, shoot positioning, and 33% defoliation) on these processes were investigated under field conditions. An increase in starch concentration of basal leaves occurred from the morning to the afternoon during the most active vegetative growth period (up to veraison), indicating a proportional change in storage or export of assimilates between day and night. During later developmental stages diurnal starch levels slightly declined or remained the same. Seasonally, leaf starch remained relatively stable until veraison, whereafter it increased, reaching highest concentrations at the post-harvest stage. Canopy management generally increased leaf starch concentrations. Berries contained no significant amounts of starch. Root starch concentrations were usually higher than those of leaves. Diurnally as well as seasonally, root starch accumulation patterns coincided with those of leaves, indicating a close relationship between source and sink tissue. Canopy management resulted in stable diurnal root starch concentrations without affecting the daily mean starch level; afternoon values of treated vines were, however, generally lower. The results imply that carbohydrate supply and starch-synthesising enzyme systems were not limited by manipulating the canopy and decreasing foliage. It seems, however, that particularly late in the season starch accumulation in roots may be delayed by canopy manipulation as applied. This indicates a shift in sucrose partitioning and its utilisation in roots and other sink areas, e.g. the berries, when the canopy is manipulated.